ESTRATEGIA DE VIDA PARA EL DISEÑO AGROTURISTICO DEL CANTÓN QUINSALOMA AÑO 2022 - Quiñonez Zapata, Ginger Elizabeth (2022)
The objective of this research is to develop a life strategy for the agrotourism design of the Quinsaloma canton to promote the development of agrotourism, in order to enhance this activity as a main source of the studied area, since the canton does not have agrotourism activities. in them, to obtain knowledge about agriculture. According to the methodology, it can be said that it has a mixed approach in which adequate techniques and tools were established for gathering corroborated information, such as observation sheets and surveys. Likewise, the results obtained showed that the demand is interested in the agrotourism activity. On the other hand, a life strategy is presented for the agrotourism design of the Quinsaloma canton in order to strengthen rural and urban tourism development, thus raising awareness among tourists and inhabitants. in knowing more about nature and increasing tourism in the place.